Rearticulating Rhetorical Modes of Apologies in Academic Texts: EFL University Students' Voices - Anselmus Sudirman; J. C. Setyo Karjono (TAMANSISWA INTERNATIONAL JOURNAL IN EDUCATION AND SCIENCE, 2020)
The objectives of this research are 1) to describe the frequencies of rhetorical modes of apologies in academic texts written by EFL university students, and 2) to find out problems that they face when constructing rhetorical modes of apologies through exposition, narration, description and argumentation genres of writing. Using documents and interviews, this qualitative research mainly deals with the purposive sampling technique, data reduction, and display concerning rhetorical modes of apologies and problems on constructing them. The research results show that the interpretation of students' rhetorical expressions is meta-pragmatic based on interactions, linguistic nuances, and rhetorical meanings. Rhetorical modes of apologies influence the language production, contextual expressions, and dissemination of messages to audiences or readers. The language used in the rhetorical modes of apologies is integrally connected to one's identity, personality, and situation. Therefore, several efforts are made to see how linguistic differences in a series of interactions lead to denials, avoidance of responsibility, reduction of offensiveness, corrective action, and mortification. The interview results outline that rhetorical modes of apologies function as an integral part of interests, utilities, and moral values instead of some problems the students faced while writing the academic texts.